Species Distribution Modelling Using Bioclimatic Variables on Endangered Endemic Species (Bubalus depressicornis and Bubalus quarlesi) - Septianto Aldiansyah; Khalil Abdul Wahid (Department of Geography Education, University of Jember, 2023)
Sulawesi Island is an island located in the Wallacea area. Most of the fauna on the island of Sulawesi is a transitional fauna from Australia and Asia. This study aims to model the potential distribution of the species Bubalus depressicornis and Bubalus quarlesi using famous models in the present and in the future as a result of climate change phenomena throughout the island of Sulawesi and beyond their natural habitat. The parameters used are bioclimatic variables and in-situ presence data. The method used is Maximum Entropy by comparing the GLM, SVM, and RF algorithms. The model is evaluated with reference to the values of AUC, COR, TSS, Deviance, and observation data. The RF model is quite good in modeling the distribution of B. depressicornis and B. quarlesi species with AUC values of 0.92 and 1, COR values of 0.59 and 0.84, TSS values of 0.87 and 1, and Deviance values of 0.37 and 0.08, respectively, while the results of data observations show values of 80% and 84%. B. depressicornis was most affected by bio14=0.665, while B. quarlesi was most affected by bio2=0.525, which means that this endemic species is suitable to live in a tropical climate with a warm and wet climate throughout the year, where the difference in temperature at night and during the day is very large. In the future, B. depressicornis and B. quarlesi are estimated to be compatible in an area of 143,281.78 km2 (81%) and 136,892.89 km2 (77%) of the Sulawesi.